Penggelapan Dana Nasabah Melalui Pemindahbukuan Nominal Kecil: Kajian Normatif Atas Pelaku, Penyertaan, dan Pertanggungjawaban Perbankan - Nurdian syah (Jurnal Hukum Lex Generalis, 2025)
This study examines the criminal liability of bank employees who abuse their authority by transferring customers’ funds in relatively small amounts, including the potential involvement of other parties within the bank’s internal structure. The research employs a normative legal method with a statutory approach. The analysis shows that such conduct constitutes embezzlement in office under Law Number 1 of 2023 on the Criminal Code, regardless of the amount of loss incurred, and may involve participation through role distribution or omission. Therefore, strengthening internal control mechanisms, conducting regular audits, and limiting transactional authority are necessary to prevent similar offenses.